Sulodexide in venous disease. (7th December 2018) - Carroll, B. J.; Piazza, G.; Goldhaber, S. Z.
Abstract : Summary: Sulodexide is a glycosaminoglycan extracted from porcine intestinal mucosa. The purpose of this review is to discuss sulodexide's complex pharmacological profile and its clinical applications for venous disease. Sulodexide has wide‐ranging biological effects on the vascular system, including antithrombotic, profibrinolytic, anti‐inflammatory, endothelial protective and vasoregulatory effects. Sulodexide has emerged as a potential therapeutic option for the management of chronic venous insufficiency, including venous ulceration, and the prevention of recurrent venous thromboembolism, with a low rate of major bleeding complications. Sulodexide's pleiotropic vascular effects may facilitate the management of common venous disorders.